The Design of a Microcontroller-based Automatic Liquid Level Control System - Ahmad, Saleh; Al Rahman Abu Ebayyeh, Abd; Alhashmi, Abdulaziz (International Journal of Engineering and Technology, 2019)
In this paper, a liquid level control system was designed and fabricated. Control of the liquid level was accomplished by adjusting the sup-ply voltage to a centrifugal pump that is delivering the liquid from a reservoir tank to an upper tank. The liquid level control system was implemented on an ATmega328 microcontroller. Three control strategies are implemented, manual mode, ON/OFF controller, and PID controller. Serial communication is used to establish the communication between the ATmega328 and a computer running MATLAB soft-ware. A graphical user interface was constructed to allow users to interact with the system. The system model is obtained using an experi-mental approach. The obtained model is then used for the design of the PID controller. Experimental results are provided to highlight the performance of the implemented controllers. Â Â